Assessment of the digital transformation of European countries with small open economies - Goloventchik, Galina G.; Zhyrkevich, Anhelina B. (Journal of the Belarusian State University. Economics, 2021)
The article is based on the criteria proposed by professor E. L. Davydenko, in which European countries with small open economies are selected. A rating analysis of countries with small economies situation based on well-known international indices that characterise the level of digital economy development is carried out. A new formula is proposed for calculating country average position in the final rating of digital transformation level. The analysis of digital transformation level of countries with small economies using the cluster approach is carried out.